Environmental Analysis of Burning Occurrence in Northeast Area of Cerrado - Resende, Fernanda Cristina; Cardozo, Francielle da Silva; Pereira, Gabriel (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2017)
Through the increase of the agricultural areas, the Cerrado biome has become one of the most favorable environments for the expansion of the Brazilian’s agricultural frontier. One of the consequences is the deforestation and the increase of the number of fires, leading to the degradation and suppression of large areas of natural ecosystems in this biome. Consequently, the objective of this study was to analyze the spatial distribution of the burned areas in northeast area of Cerrado. For this purpose, the mapping of the burned areas in MODIS sensor images was performed for the 2012 to 2015 years, using the Linear Spectral Mixture Model (LSMM). The rainfall data from the Tropical Rainfall Measuring Mission (TRMM) were used to verify the influence of rainfall on burning occurrence. In addition, the occurrence and frequency of burnings were analyzed with the land use and land cover, with the conservation units and with the counties located in the study area. From the burned areas mapping in MODIS sensor images it was verified that the areas most affected by fires are Savannas, Grasslands and Woody Savannas. The precipitation data showed that the years with the lowest precipitation rates were also the years with the highest incidence of burned areas. The conservation unit most affected was the Uruçuí-Una, an Ecological Station located in Piauí, with an average of 36.5% of its area burned and the municipalities most affected are located mainly in the states of Piauí and Maranhão, with half of their areas burned in average.